2022
DOI: 10.1001/jamanetworkopen.2022.23803
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Revision Surgery After Decompression With vs Without Fusion Among Patients With Degenerative Lumbar Spinal Stenosis

Abstract: IMPORTANCEOnly limited data derived from large prospective cohort studies exist on the incidence of revision surgery among patients who undergo operations for degenerative lumbar spinal stenosis (DLSS). OBJECTIVE To assess the cumulative incidence of revision surgery after 2 types of index operations-decompression alone or decompression with fusion-among patients with DLSS. DESIGN, SETTING, AND PARTICIPANTS This cohort study analyzed data from a multicenter, prospective cohort study, the Lumbar Stenosis Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…Ulrich and colleagues found incidences of revision operations consistent with rates in the Swedish and Norwegian trials and suggested that the use of different decompression techniques may explain the higher rate of revision operations in the US trial . In the Swedish and Norwegian trials, microdecompression was performed, whereas complete laminectomy was performed in the US trial.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Ulrich and colleagues found incidences of revision operations consistent with rates in the Swedish and Norwegian trials and suggested that the use of different decompression techniques may explain the higher rate of revision operations in the US trial . In the Swedish and Norwegian trials, microdecompression was performed, whereas complete laminectomy was performed in the US trial.…”
mentioning
confidence: 90%
“…In an observational study based on data from the Swiss Lumbar Stenosis Outcome Study, Ulrich and colleagues evaluated the incidence of revision operation in the first 3 years after surgery for degenerative lumbar spinal stenosis. Their study included patients with and without a concomitant degenerative spondylolisthesis (ie, a forward slip of 1 vertebra relative to the vertebra below).…”
mentioning
confidence: 99%
“…Sometime after the surgery, there are both back and limb pain, as well as neurological deficits. Second lumbar stenosis yields worse results, and patients have better treatment results after 1 surgery than after 2 [ 93 , 94 ]. The frequency of repeated decompression is 9.3–28%.…”
Section: Rehabilitation Treatment Of Patients With Degenerative Lumba...mentioning
confidence: 99%
“…The frequency of repeated decompression is 9.3–28%. For every 100 patients, 16 have experienced recurrent stenosis on the operated level or higher [ 93 , 94 ]. The longer the observation time after the original decompressive laminectomy, the higher the percentage of repeated surgeries [ 93 , 94 ].…”
Section: Rehabilitation Treatment Of Patients With Degenerative Lumba...mentioning
confidence: 99%
See 1 more Smart Citation